Accountants' Competencies for Sustainability Reporting: An Exploratory Study - Maria-Silvia Fota; Nicoleta-Elena Cristea; Alexandru Ureche; Nadia Albu (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- What is the perception of various groups about the accountants' competencies in relation to sustainability reporting? Motivation- Extant research provides conflicting views on the role of accountants in sustainability reporting, their competencies and the role of various actors in developing the necessary skills. Data- We employed an online questionnaire-based survey that was administered to various professional groups, including students, accountants, non-accountants and professors. The final sample comprised 168 responses. Tools- Cross-sectional analyses were further used to statistically analyze the data. Cross-sectional analyses aimed to indicate the differences between sub-groups of respondents. Findings- We test the perceived importance of the expected competencies for the accounting profession (IFAC, 2023) and find that the order of decreasing importance is traditional technical accounting competencies, soft skills and finally sustainability-related competencies. Respondents expect that all three actors investigated, i.e. universities, professional associations and employers to play a very important role in forming the competencies accountants need to possess in nowadays' environment, with professional associations expected to play a significant role. Surprisingly, professors perceive that all categories of skills are more important, compared to other categories and particularly to accountants. Non-accountants attach a lower importance than other groups to the need of soft skills and sustainability related skills in the accounting profession. Contribution- Our study contributes to the literature on the role of accountants in sustainability accounting and reporting by incorporating the recent developments in the profession and by offering a more recent view of professionals. Moreover, we investigate the perception of various groups (students, accountants, non-accountants and accounting academics), which offers a richer perspective than studies focused on one group. Research limitations- Limitations are related to the inherent constraints associated with employing surveys, including small sample size, and limited generalizability.
Keywords: M41; 650; sustainability reporting; competencies; accounting profession; survey